(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
A sequence of sub-subzonal correlative units at the level of biohorizon is described for the Subboreal Province, Lower Toarcian of North Yorkshire, north west England. Nineteen such units are recognised, as follows: Tenuicostatum Chronozone, Paltum Subchronozone (paltum), Clevelandicum Subchronozone (crosbeyi, clevelandicum), Tenuicostatum Subchronozone (tenuicostatum), Semicelatum Subchronozone (semicelatum, antiquum), Serpentinum Chronozone, Exaratum Subchronozone (elegantulum, exaratum, elegans), Falciferum Subchronozone (pseudoserpentinum, falciferum), Bifrons Chronozone, Commune Subchronozone (ovatum, commune, athleticum), Fibulatum Subchronozone (turriculum, braunianus, vortex), Crassum Subchronozone (crassum-bifrons, crassum-semipolitum). The presence of shared taxa permits detailed correlations to be established with submediterranean zonal schemes in more southerly areas of Europe and an equilibration of zonal boundaries across the region is therefore proposed, providing a uniformity of interpretation for the European Lower Toarcian.